2019
DOI: 10.1007/s10833-019-09359-x
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent accountability in schools: A study of how school leaders work with the implementation of assessment for learning

Abstract: In response to accountability systems dominated by external inspections and achievement data, calls are being made for intelligent accountability or a new accountability paradigm that focuses on meaningful learning, enabled by professionally skilled and committed educators within the system. In such systems, the actors are encouraged to strive for continuous development in learning organisations based on teamwork, distributed leadership, and professional learning communities. School leaders are positioned betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
0
10
0
6
Order By: Relevance
“…The demands of inclusion are significant and add to the high demands of teachers' accountability for students' achievement [54][55][56]. These demands might generate high levels of stress and burnout and the inability to cope with classroom challenges [57][58][59].…”
Section: Teachers' Professional Development To Work With Sensmentioning
confidence: 99%
“…The demands of inclusion are significant and add to the high demands of teachers' accountability for students' achievement [54][55][56]. These demands might generate high levels of stress and burnout and the inability to cope with classroom challenges [57][58][59].…”
Section: Teachers' Professional Development To Work With Sensmentioning
confidence: 99%
“…Intelligent school environments provide a platform for increasing student's motivation, and enable students to learn efficiently. Moreover, in intelligent schools, the teaching-learning process is not limited to the hours of students attending school and students can learn and practice curriculum concepts outside school through the use of content management systems [11]. Using application teacher, students and parents can collaborate on a single podium, while teachers can counsel students in a real-time and share interact with parents as well as administrators [25].…”
Section: The Importance Of Teaching-learning Dimensionmentioning
confidence: 99%
“…The use of ICT in education in intelligent schools increases student's motivation and educational achievement, in addition; it reduces student interactions and students' dependency on school [9,10]. The results of the study concerning the differences and effects of education in intelligent schools compared to traditional schools revealed that in intelligent school students' motivation, learning skills, and educational accomplishment is higher than students in traditional school [11].…”
Section: Introductionmentioning
confidence: 97%
“…Principals are seen as a key factor to improve school effectiveness and performance (Day et al, 2016). The role of the principal in this position is unique because it is located between the public and internal areas of the school (Tolo et al, 2020), so that the principal in carrying out his leadership function requires the support, trust, and active involvement of all components (Sebastian et al, 2019), as well as creativity in innovating and advancing schools and improving student learning outcomes (Pietsch et al, 2019;Zhang et al, 2018;Heck & Hallinger, 2014).…”
Section: Introduction *mentioning
confidence: 99%